Intermittent environmental exposure to hydrogen prevents skin photoaging through reduction of oxidative stress. Issue 4 (20th February 2023) - Kiyoi, Takeshi; Liu, Shuang; Takemasa, Erika; Hato, Naohito; Mogi, Masaki
Abstract : Aim: Molecular hydrogen is not only expected to be used as an energy‐generating resource, but also to have preventive effects on a variety of clinical manifestations related to oxidative stress through scavenging radicals or regulating gene expression. In the current study, we investigated the influence of intermittent environmental exposure to hydrogen gas at a safe concentration (1.3%) on photoaging using an ultraviolet A (UVA)‐irradiated murine model. Methods: To mimic the expected human daily activity cycle, UVA exposure in the daytime and hydrogen exposure in the night‐time, an original design, UVA‐transmission, hydrogen‐exposure system was established. Mice were bred under experimental conditions of UVA irradiation and normal air for 8 h (outdoor time 09.00–17.00 hours), and UVA non‐irradiation and inhalation of hydrogen gas for 16 h (indoor time 17.00–09.00 hours), and the daily cycle was continued for up to 6 weeks. The progression of photoaging, including morphological changes, collagen degradation and UVA‐related DNA damage, was evaluated. Results: Intermittent administration of hydrogen gas by our system prevented UVA‐induced epidermal signs, such as hyperplasia, melanogenesis and appearance of senescence cells, and UVA‐induced dermal signs, such as collagen degradation. In addition, we detected attenuation of DNA damage in the hydrogen exposure group as indirect evidence that intermittent exposure to hydrogen gas reduced oxidative stress. Conclusions: Our findings support the notion that long‐term, intermittent environmental exposure to hydrogen gas in daily life has a beneficial effect on UVA‐induced photoaging. Geriatr Gerontol Int 2023; 23: 304–312 . Abstract : The present study investigated whether intermittent environmental exposure to 1.3% hydrogen assuming the human daily activity cycle has a beneficial effect on skin photoaging through the reduction of oxidative stress in ultraviolet A (UVA)‐induced skin photoaging model mice. Mice were bred under UVA irradiation in normal air for 8 h (outdoor time 09.00–17.00 hours), and non‐UVA‐irradiation in inhalation of 1.3% hydrogen gas for 16 h (indoor time 17.00–09.00 hours). The daily cycle was continued up to 6 weeks. Consequentially, the hydrogen administration system prevented UVA‐induced photoaging signs, such as visible change of surface texture, epidermal hyperplasia, epidermal cell proliferation, epidermal melanogenesis and dermal collagen degradation, after reduction of UVA‐related DNA damage as an index of oxidative stress.